2022
DOI: 10.3389/fpls.2022.908342
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Nature of Hybrid Sterility and Divergence of Asian Cultivated Rice

Abstract: Intraspecific hybrid sterility is a common form of postzygotic reproductive isolation in Asian cultivated rice, which is also the major obstacle to utilize the strong heterosis in the rice breeding program. Here, we review recent progress in classification and hybrid sterility in Asian cultivated rice. A genome-wide analysis of numerous wild relatives of rice and Asian cultivated rice has provided insights into the origin and differentiation of Asian cultivated rice, and divided Asian cultivated rice into five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…One of the major challenges in breeding Basmati varieties is hybrid sterility. Hybrid sterility is known to occur in crosses between japonica and indica varieties [ 52 , 53 ], and Basmati varieties have been reported to be hybrid sterile with japonica and indica varieties [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major challenges in breeding Basmati varieties is hybrid sterility. Hybrid sterility is known to occur in crosses between japonica and indica varieties [ 52 , 53 ], and Basmati varieties have been reported to be hybrid sterile with japonica and indica varieties [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have reported outbreaks of blast disease in the Basmati variety in Kenya [ 5 , 9 ]. The breeding of Basmati varieties for blast resistance has not progressed much, mainly because of the hybrid sterility between Basmati varieties and japonica or indica rice [ 10 ]. Therefore, it is important to improve blast resistance in the Basmati variety.…”
Section: Introductionmentioning
confidence: 99%
“…Asian cultivated rice, the most important cultivated species in the AA genome rice species of the genus Oryza, mainly comprises two subspecies, indica and japonica (Kato 1930;Hikoichi 1952), and some relatively small ecological subgroups. Currently, most studies classi ed Asian cultivated rice into ve subgroups based on molecular biology, genomics, and other characteristics: temperate japonica, tropical japonica, indica, aus and basmati (Glaszmann 1987 Zhang et al 2022). Numerous studies and breeding practices shown that the hybridization-introgression of subgroups within Asian cultivated rice played a very important role and had great potential for the utilization of heterosis and the improvement of rice yield, quality, and resistance (Brar et Kiran et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 30 genes/QTLs conferring sterility in inter-subspeci c hybrids in Asian cultivated rice were reported ( Zhou et al 2023). Twenty-two hybrid sterility loci were described between indica and temperate japonica cultivars, including major genes such as S5, Sa, Sc, RHS12/Pf12/Se (Zhang et al 2022). In addition to indica and temperate japonica, some hybrid sterility loci were also found in other subgroups of Asian cultivated rice.…”
Section: Introductionmentioning
confidence: 99%